Autologous Transplantation as Consolidation for High Risk Aggressive T-Cell Non-Hodgkin's Lymphoma: A SWOG 9704 Intergroup Trial Subgroup Analysis - Al-Mansour, Zeina (Leuk Lymphoma, 2019)
Phase II data suggest a benefit to autotransplantation for aggressive T-NHL in first remission; randomized trials have yet to validate this. We performed a retrospective analysis of aggressive T-NHL patients in the intergroup randomized consolidative autotransplant trial (SWOG 9704). Of the 370 enrolled, 40 had T-NHL: 12 were not randomized due to ineligibility (n=1), choice (n=2), or progression (n=9), leaving 13 randomized to control and 15 to ASCT. Two ASCT patients refused transplant and one failed mobilization. The 5-year landmark PFS/OS estimates for ASCT vs control groups were 40% vs 38% (p=0.56) and 40% vs 45% (p=0.98), respectively. No difference was seen based on IPI, or histologic subtype. Only 1/7 receiving BCNU-based therapy survived versus 4/5 receiving TBI. Aggressive T-NHL autotransplanted in first remission did not appear to benefit from consolidative ASCT. This and the 30% who dropped out pre-randomization mostly to progression, suggests that improved induction regimens be developed.